Omega-3 and omega-6 polyunsaturated fatty acids and their potential therapeutic role in protozoan infections - Rahman, Sajid Ur; Weng, Tzu-Nin; Qadeer, Abdul; Nawaz, Saqib; Ullah, Hanif; Chen, Chien-Chin (Frontiers in Immunology, 2024)
Protozoa exert a serious global threat of growing concern to human, and animal, and there is a need for the advancement of novel therapeutic strategies to effectively treat or mitigate the impact of associated diseases. Omega polyunsaturated fatty acids (ω-PUFAs), including Omega-3 (ω-3) and omega-6 (ω-6), are constituents derived from various natural sources, have gained significant attention for their therapeutic role in parasitic infections and a variety of essential structural and regulatory functions in animals and humans. Both ω-3 and ω-6 decrease the growth and survival rate of parasites through metabolized anti-inflammatory mediators, such as lipoxins, resolvins, and protectins, and have both in vivo and in vitro protective effects against various protozoan infections. The ω-PUFAs have been shown to modulate the host immune response by a commonly known mechanism such as (inhibition of arachidonic acid (AA) metabolic process, production of anti-inflammatory mediators, modification of intracellular lipids, and activation of the nuclear receptor), and promotion of a shift towards a more effective immune defense against parasitic invaders by regulation the inflammation like prostaglandins, leukotrienes, thromboxane, are involved in controlling the inflammatory reaction. The immune modulation may involve reducing inflammation, enhancing phagocytosis, and suppressing parasitic virulence factors. The unique properties of ω-PUFAs could prevent protozoan infections, representing an important area of study. This review explores the clinical impact of ω-PUFAs against some protozoan infections, elucidating possible mechanisms of action and supportive therapy for preventing various parasitic infections in humans and animals, such as toxoplasmosis, malaria, coccidiosis, and chagas disease. ω-PUFAs show promise as a therapeutic approach for parasitic infections due to their direct anti-parasitic effects and their ability to modulate the host immune response. Additionally, we discuss current treatment options and suggest perspectives for future studies. This could potentially provide an alternative or supplementary treatment option for these complex global health problems.